Pengaruh Konten Kreatif, Engagement Rate, Trust in Influencer Terhadap Brand Engagement Lagilah.id - Suci Amalia Ramadhani; Nurilahi .; Bobby Hartanto; Willy Cahyadi (CV. ITTC INDONESIA, 2026)
The development of digital marketing has encouraged MSMEs in Indonesia to adopt influencer marketing strategies to enhance brand engagement amid increasingly intense competition in the digital market. This study aims to analyze and empirically examine the effect of creative content, engagement rate, and trust in influencer on brand engagement at SME Lagilah.id in Medan City. This study is a causal quantitative research with a survey approach. The population of this study is Instagram followers of MSMEs Lagilah.id from Generation Z and Millennials. A sample of 112 respondents was selected using purposive sampling technique. Primary data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS. Creative content has a positive and significant effect on brand engagement (path coefficient = 0.233; T-statistics = 2.085). Engagement rate has a positive and significant effect (path coefficient = 0.277; T-statistics = 3.074). Trust in influencer has the greatest effect (path coefficient = 0.448; T-statistics = 4.434). The three variables simultaneously explain 72.4% of the variance in brand engagement. Influencer marketing strategies that integrate creative content, engagement rate, and consumer trust are proven to be an effective approach for local SMEs in enhancing brand engagement in the digital era. These findings recommend that MSMEs prioritize collaboration with authentic influencers who are capable of driving real audience interaction.